Comparative proteomics reveals recruitment patterns of some protein families in the venoms of Cnidaria. (October 2017) - Jaimes-Becerra, Adrian; Chung, Ray; Morandini, André C.; Weston, Andrew J.; Padilla, Gabriel; Gacesa, Ranko; Ward, Malcolm; Long, Paul F.; Marques, Antonio C.
Abstract: Cnidarians are probably the oldest group of animals to be venomous, yet our current picture of cnidarian venom evolution is highly imbalanced due to limited taxon sampling. High-throughput tandem mass spectrometry was used to determine venom composition of the scyphozoan Chrysaora lactea and two cubozoans Tamoya haplonema and Chiropsalmus quadrumanus . Protein recruitment patterns were then compared against 5 other cnidarian venom proteomes taken from the literature. A total of 28 putative toxin protein families were identified, many for the first time in Cnidaria. Character mapping analysis revealed that 17 toxin protein families with predominantly cytolytic biological activities were likely recruited into the cnidarian venom proteome before the lineage split between Anthozoa and Medusozoa. Thereafter, venoms of Medusozoa and Anthozoa differed during subsequent divergence of cnidarian classes. Recruitment and loss of toxin protein families did not correlate with accepted phylogenetic patterns of Cnidaria. Selective pressures that drive toxin diversification independent of taxonomic positioning have yet to be identified in Cnidaria and now warrant experimental consideration. Highlights: Early diverging metazoans offer a phylogenetic anchor to study evolution of the venom trait. Venom proteomes of the medusozoans Chrysaoralactea, Tamoya haplonema and Chiropsalmus quadrumanus are presented. Toxin recruitment and retention patterns do not always correlate with accepted phylogeny. Factors that drive toxin diversification independent of phylogeny merit closer scrutiny.